Investigating the Knowledge, Attitudes, and Practices of Interns in the Workplace - Obinna Nwokike (Universitas Ahmad Dahlan, 2022)
Since internships are recognized forms of workplace learning, this study investigated their impact on the knowledge, attitude, and practices of interns. A paired t-test quasi-experiment (pretest/post-test) was carried out on the sample of 137 interns in university libraries in Edo State, Nigeria using a questionnaire. The study found that the interns had improved their knowledge, attitudes, and practices post-intervention. The statistically significant results imply that the internship was an effective intervention that improved the interns' knowledge, attitude, and practice. In conclusion, the study considered the implications of practicing librarians and Library and Information Science educators uniting to develop and implement structured interventions. It recommended replicating this intervention in other states to improve the knowledge, attitude, and practical skills of interns and ensure they are effective in the workplace.